Inter-regional differences in body proportions in Indian children and adolescents-a cross-sectional multicentric study - Smruti Vispute; Vaman Khadilkar; Anuradha Khadilkar; Veena Ekbote; Narendra Singh; Shashi Chiplonkar (Taylor & Francis Group, 2020)
Background: Sitting height (SH) and leg length (LL) help in assessing disproportionate growth. Anthropometric dissimilarity has been observed in different ethnicities. Aim: To (1) study sitting height and body proportions in children from different regions of India; and (2) compare sitting height and body proportions with data from other countries. Subjects and methods: This was a cross-sectional multicentric observational study, where 7961 (4328 boys) 3-18 year old children from five regions (north, south, east, west and central) were measured (height, weight and SH). Results: Boys from north India and girls from central India were taller and heavier (mean height 153.2 ± 18, 146.4 ± 11), while western boys and girls were the shortest (131.1 ± 20.7, 129.8 ± 19.5) (p < 0.05 for all). The highest SH was observed in the north (79.2 ± 8.5) and the lowest in the west (68.8 ± 9.1). Mean SH:LL ratio was highest in children from the northeast (1.13) followed by those from western, northern and central India (1.12, 1.10 and 1.07, respectively) and the ratio was the least in children from south India (1.05) (p < 0.0.5 for all except northeast and west). Children from the north and west were similar to the Dutch, children from the south were similar to South (black) Africans and the north-eastern children were similar to Chinese children. Conclusion: There were inter-regional differences in body proportions; similarities in body proportions with children from other ethnicities may throw light on the migration history of Indian people.